Lernwerkstattarbeit als Prinzip Möglichkeiten für Lehre und Forschung - Kekeritz, Mirja; Graf, Ulrike; Brenne, Andreas; Fiegert, Monika; Gläser, Eva; Kunze, Ingrid (Lernen und Studieren in Lernwerkstätten. Impulse für Theorie und Praxis, 2017)
The present work "Lernwerkstatt als Prinzip - Möglichkeiten für Lehre und Forschung" (Learning Workshop as Principle - Possibilities for Teaching and Research), as the third volume of the series "Lernen und Studieren in Lernwerkstätten" (Learning and Studying in Learning Workshops), takes up the question of the possibilities of the principle of learning workshop work as a productive moment of developments in higher education didactics. Currently, there are controversial efforts to place the education of future pedagogues and educational scientists in a closer practical and research context. In this context, learning workshops as higher education institutions play a central role. Despite diverse forms and foundations, university learning workshops are united by a fundamental understanding: learning workshop work as a principle. In the contributions to this volume, the authors explore the potential of learning workshops for teaching and research in the context of science.